Analisis Kerjasama Indonesia-Belanda dalam Kasus Hilangnya Kapal De Ruyter, Java, dan Kortenaer di Perairan Indonesia - Wandasari, Dwi Arum; Putranti, Ika Riswanti; Basith Dir, Andi Akhmad (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2018)
The existence of De Ruyter, Java, and Kortenaer site ships was discovered in Indonesian waters in 2002 for the first time. To commemorate the 75th anniversary of the sinking boats, Indonesia had dived once again into the waters in 2016. Because of the aforementioned dived, Netherlands received a report that all the three ships have gone. Therefore, Indonesia and Netherlands relations has been heat up. However, this problem can be solved through Indonesia and the Netherlands cooperation in join verification of the three Netherlands ships. This research used the concept of national interest and theory of compliance in order to explain why Indonesia and Netherlands cooperate in solving the missing ships. The result shows that Netherlands has an interest in the cooperation undertaken with the Indonesia.. It includes how Indonesia asked the Netherland to protect Kortenaer ships that are still under the water and to rearrange the managerial heritage of underwater culture that has bad image in international stage. Both collaborations are conducted as a form of state compliance with UNCLOS 1982 which has the principle of water civic cultural citizenship that must be done together.